Exploring CBR workers’ perceptions of their role in wheelchair provision in three areas of Uganda - Seymour, Nikola (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil (Rehabilitation))--Stellenbosch University, 2016.